2014
DOI: 10.1177/0956797613519270
|View full text |Cite
|
Sign up to set email alerts
|

Later Maturation of the Beneficial Than the Detrimental Effect of Selective Memory Retrieval

Abstract: In adults, selective memory retrieval can both impair and improve recall of other memories. The study reported here examined whether children also show these two faces of memory retrieval. Employing a variant of the directedforgetting task, we asked second, fourth, and seventh graders to study a list of target and nontarget words. After study, the participants received a cue to either forget or continue remembering the list. We subsequently asked some participants to recall the nontarget words before we tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…In such case, the reactivated context information may no longer be maintained in working memory and the effectiveness of the context cue in searching for the target items be reduced (e.g., Polyn et al, 2009). The other study (Aslan & Bäuml, 2014) demonstrated that the beneficial effect of memory retrieval is present in seventh graders, but is still absent in second and fourth graders, indicating that the capability to capitalise on retrieval-induced context reactivation emerges relatively late in development, which coincides with the finding that WMC continues to develop until adolescence (Case et al, 1982;Siegel, 1994). The present finding on the role of WMC for the beneficial effect of selective retrieval relates to recent research on the contiguity effect.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…In such case, the reactivated context information may no longer be maintained in working memory and the effectiveness of the context cue in searching for the target items be reduced (e.g., Polyn et al, 2009). The other study (Aslan & Bäuml, 2014) demonstrated that the beneficial effect of memory retrieval is present in seventh graders, but is still absent in second and fourth graders, indicating that the capability to capitalise on retrieval-induced context reactivation emerges relatively late in development, which coincides with the finding that WMC continues to develop until adolescence (Case et al, 1982;Siegel, 1994). The present finding on the role of WMC for the beneficial effect of selective retrieval relates to recent research on the contiguity effect.…”
Section: Discussionmentioning
confidence: 95%
“…We expected to replicate previous work by finding a detrimental effect of preceding nontarget retrieval after the counting task, i.e., in the absence of a context change, but a beneficial effect of preceding nontarget retrieval after the imagination task, i.e., in the presence of a context change (e.g., Bäuml & Samenieh, 2012). More important, following the view that the beneficial effect of retrieval is mediated by context-reactivation processes (Bäuml & Dobler, in press;Bäuml & Samenieh, 2012) and previous work suggesting a positive relationship between WMC and the capability to capitalise on retrievalinduced context reactivation (Aslan & Bäuml, 2014;Dobler & Bäuml, 2012), we further expected high-WMC individuals to show a larger beneficial effect of retrieval than low-WMC individuals. If previous findings obtained with the retrieval-practice task generalised to the present output-interference task, a positive relationship should also arise between WMC and the detrimental effect of selective retrieval.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…The finding is commonly attributed to either an inhibitory process, assuming that the forget cue inhibits access to the first list's study context (e.g., Geiselman, Bjork, & Fishman, 1983), or a noninhibitory process, assuming that the forget cue induces a change in subjects' mental context and thus, for the firstlist items, creates a contextual mismatch between study and test (e.g., Sahakyan & Kelley, 2002). Employing this task, Bäuml and colleagues (Aslan & Bäuml, 2014;Bäuml & Samenieh, 2010 recently showed that when the items of the first list, unbeknownst to participants, consist of predefined target and nontarget items, then prior recall of the nontargets at test impairs individuals' target recall in the remember condition, but improves individuals' target recall in the forget condition, thus showing two faces of selective memory retrieval. Experiment 1 examines whether the same two faces of selective memory retrieval are present when pairs of subjects recall the items of the first list and target recall of a listener follows preceding nontarget recall of a speaker.…”
Section: Methodsmentioning
confidence: 97%
“…During the learning phase, participants were instructed to forget some items after having encoded them, whereas other items were to be retained for the later test. RIF did not occur for to-be-forgotten items, but only for to-be-retained items (see also Aslan & Bäuml, 2014;Bäuml & Samenieh, 2010. This finding suggests that lowered accessibility due to intentional forgetting prevented competition.…”
mentioning
confidence: 91%